YouTube's Implementation As an Alternative Media for Information Literacy Learning for Students at Pelita Harapan University - Wahyudi, Phillips Iman Hery (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: the use of the YouTube platform as a medium for learning information literacy in students.Purpose: to find out the implementation and use of the YouTube platform as a learning medium to help students understand information literacy.Method: Using a qualitative descriptive method with the analysis of the Miles and Huberman model approach, namely data reduction, data presentation and conclusion drawing.Findings: Using YouTube as an information literacy learning media helps students understand information literacy material, this can be seen from the average access to information literacy material above 5000 times.Conclusion: YouTube can be used as a medium for learning information literacy even though it is a supplement or supplement.Â